2017
DOI: 10.1124/jpet.117.242107
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and Genetic Polymorphism Contribute to Variability in Acetaminophen Pharmacokinetics, Metabolism, and Protein-Adduct Concentrations in Healthy African-American and European-American Volunteers

Abstract: Over 30 years ago, black Africans from Kenya and Ghana were shown to metabolize acetaminophen faster by glucuronidation and slower by oxidation compared with white Scottish Europeans. The objectives of this study were to determine whether similar differences exist between African-Americans and European-Americans, and to identify genetic polymorphisms that could explain these potential differences. Acetaminophen plasma pharmacokinetics and partial urinary metabolite clearances via glucuronidation, sulfation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 25 publications
1
39
2
2
Order By: Relevance
“…However, recent evidence suggests a pharmacogenomic influence. For example, there is evidence that the CYP2E1*1D polymorphism results in slower APAP oxidative metabolism …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent evidence suggests a pharmacogenomic influence. For example, there is evidence that the CYP2E1*1D polymorphism results in slower APAP oxidative metabolism …”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that the CYP2E1*1D polymorphism results in slower APAP oxidative metabolism. 27 Alternatively, susceptibility may be because of a non-CYP-mediated mechanism, such as lower hepatic glutathione stores. In animal models, decreased glutathione stores predispose to the development of hepatocellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…CL/F and V z /F of metabolites were not calculated. Simulations of a multiple dosing regimen (650 mg every 4 hours) were performed using the average of the estimated compartmental parameters from pre‐ and post‐RYGBS data from this study and published data from healthy volunteers …”
Section: Methodsmentioning
confidence: 99%
“…Metabolism of APAP can be influenced by genotype differences, and variations in glucuronidation are seen in different populations due to polymorphisms in the UDP-glucuronosyltransferase (UGT) enzymes. It was recently shown that UGT2B15 *2/*2 genotype subjects showed higher APAP protein-adduct concentrations than *1/*2 and *1/*1 individuals 10 . Formation of APAP protein adducts and their release into the circulation are now areas of intense study due to the clinical implications in management of patients with APAP overdose, mainly since APAP protein adducts have been suggested to be biomarkers useful for diagnosing an APAP overdose 11 .…”
Section: Metabolism Of Acetaminophenmentioning
confidence: 97%